Zagadnienie identyczności w "Traktacie"> Wittgensteina - Michalski, Jakub (Filozofia Nauki, 2010)
The main goal of the paper is to present Wittgenstein’s standpoint towards the question of identity of simple things and identity sign. The starting point of the paper is the presentation of the difficulties which Russell and Frege faced while analysing „A is B„ type propositions. In the second part of the work the Wittgenstein’s thesis that identity is not a relation is examined. The thesis, which is in opposition to Frege and Russell views, within the Wittgenstein’s system, is a consequence of the ontological assumptions: atomic states of affairs (sachverhalt) are mutually independent; things are common to all possible worlds. In the next section some difficulties concerning the identity conditions on the base of Wittgenstein’s ontology, is discussed. Wittgenstein’s logical space comprises of such possible worlds that one object is able to have, within these worlds, exactly the same properties (Thesis 2.027), therefore criterion that objects are identical when they have the same properties does not apply. Furthermore within Wittgenstein’s space an object is able to change all its external properties, which means that the identity of an object cannot be determined by its external properties. However, since forms of things are ‘collective’, the internal properties do not determine the identity, as well. What does then? Wittgenstein’s argumentation supporting thesis that identity formulas are not propositions will be analysed next. The main point of the argumentation is that there is impossible to understand two names without knowing that they refer to the same thing. The last section of the article presents an idea to translate formulas including identity sign to formulas which do not comprise this sign but maintain the meaning of the ‘originals’, which is contained in Tractatus.